Craig & Fred : a Marine, a stray dog, and how they rescued each other - Grossi, Craig (William Morrow, an imprint of HarperCollinsPublishers, 2017)
Tells the uplifting true story of a U.S. Marine, the stray dog he met on an Afghan battlefield, and how they saved each other and now travel America spreading a positive message.